AI and EU border management: an antropocentric approach for all? - Gallotta, Giulia Maria (Community Notebook. People, Education and Welfare in the Society 5.0, 2025)
The essay analyses the forming lines of the EU’s approach to the development of artificial intelligence, from the 2017 European Parliament resolution to the recent AI Act and the concept of smart borders in the common migration policy. The aim is to highlight how similar instruments move in fact in opposite directions, creating profoundly different levels of rights protection for legal citizens and migrants on the one hand, and for so-called illegal migrants on the other.